Strategic advancements in tourism development in Indonesia: Assessing the impact of facilities and services using the PLS-SEM approach - Achmad, Fandi; Wiratmadja, Iwan Inrawan (Journal Industrial Servicess, 2024)
The main problem with Indonesian tourism today is the decline in the system of facilities and services that contribute to increasing tourist attractions, tourist experiences, and local economic growth. Therefore, the aim of this research is to develop a collaboration model to identify facility and service factors that influence effectiveness in tourism development. This study employs quantitative methods, utilizing purposive sampling to select small and medium enterprises (SMEs) situated in the vicinity of tourist areas. The associations among individual variables within the research model are analyzed through Partial Least Squares – Structural Equation Modeling (PLS-SEM). The research results show that spatial factors, safety and security, location, transportation, power sources, telecommunication, hospitality, promotion, clean water sources, waste management, and supporting industries positively and significantly influence tourism development. Stakeholders can focus more on planning and managing facilities and services. By paying attention to the identified factors, it is possible to increase operational efficiency and effectiveness more precisely to advance sustainable tourism development.